THE ROLE OF INNOVATIVE TEACHING METHODS IN DEVELOPING ENGLISH COMMUNICATION SKILLS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the role of innovative teaching methods in enhancing English communication skills among students. Modern education requires learners to be not only linguistically competent but also able to communicate effectively in real-life and professional contexts. The study highlights interactive teaching methods, task-based learning, project-based learning, and digital tools as effective strategies for improving speaking, listening, reading, and writing skills. The article also discusses the psychological and motivational benefits of innovative methods, such as increased learner engagement, autonomy, and confidence.